姜酮酚复配脂质伴随物对菜籽油 氧化稳定性的影响Effect of 6-paradol coordination with lipid concomitant on oxidative stability of rapeseed oil - 刘梦梦1,2，张炉1,2，肖航1,3，郭时印1,2，唐忠海1,2，范伟1,2 LIU Mengmeng1,2, ZHANG Lu1,2, XIAO Hang1,3, GUO Shiyin1,2,TANG Zhonghai1,2 ,FAN Wei1,2 (Zhongguo youzhi, 2023)
为了促进天然抗氧化剂的开发与利用，以脱除脂质伴随物多酚、甾醇和生育酚的菜籽油（空白油样）为研究对象，以DPPH自由基清除率为指标，采用正交试验优化甾醇、α-生育酚与姜酮酚复配抗氧化剂的配方。随后通过Rancimat法测定添加最优配方复配抗氧化剂的油样（简称添加姜酮酚的油样）的氧化诱导时间，并通过Schaal烘箱法考察添加姜酮酚油样的酸值、过氧化值、茴香胺值、丙二醛含量、共轭二烯含量（K232）、共轭三烯含量（K270）、总酚含量、DPPH自由基清除率和脂肪酸组成的变化，并与添加BHT的油样（以0.2 g/kg BHT代替姜酮酚）和空白油样进行了对比。结果表明：复配抗氧化剂最优配方为0.4 g/kg甾醇、0.05 g/kg α-生育酚和0.05 g/kg姜酮酚；与空白油样相比，添加姜酮酚的油样与添加BHT的油样其氧化诱导时间均延长；随着加速氧化储藏时间的延长，菜籽油的各项理化指标均发生一定程度的劣变，各油样的氧化稳定性排序为添加BHT的油样>添加姜酮酚的油样>空白油样。综上，姜酮酚复配脂质伴随物对于提高菜籽油的氧化稳定性有一定效果。 In order to promote the development and utilization of natural antioxidants, the DPPH radical scavenging rate was used as an index, and the formulation of compound antioxidants with sterols, α-tocopherols and 6-paradol was optimized by orthogonal experiment with the rapeseed oil stripped of lipid concomitant polyphenols, sterols and tocopherols as a blank oil sample. The oxidation induction time of the oil samples added with the optimum formulation of compound antioxidants (referred to as 6-paradol-added oil samples) was measured by the Rancimat method, and the changes of acid value, peroxide value, anisidine value, malondialdehyde content, conjugated diene content (K232), conjugated triene content (K270), total phenol content, DPPH radical scavenging rate and fatty acid composition of 6-paradol oil samples were investigated through the Schaal oven method. These parameters were compared with thosed of the BHT-added oil samples (0.2 g/kg BHT instead of 6-paradol ) and the blank oil samples. The results showed that the best formulation of compound antioxidant was 0.4 g/kg sterols, 0.05 g/kg α-tocopherol and 0.05 g/kg 6-paradol. Compared with the blank oil samples, the oxidation induction time of both the 6-paradol-added oil samples and the BHT-added oil samples were prolonged. With the prolonging of the accelerated oxidation storage time, all the physicochemical parameters of the rapeseed oil deteriorated in a certain extent, and the oxidative stability of the oil samples was reduced in the order: BHT-added oil samples > 6-paradol-added oil samples > blank oil samples. Therefore, the combination of 6-paradol with lipid concomitants can improve the oxidation stability of rapeseed oil.